Stigmaphyllon occidentale (Malpighiaceae), a new endemic species from Central Brazil - de Almeida, Rafael Felipe (Phytotaxa, 2016)
Stigmaphyllon occidentale is described and illustrated. This species belongs to the S. paralias complex and can be differentiated by indumentum, leaf, floral and fruit morphology. This work includes a full morphological description for the new species, along with illustrations, a distribution map, comments on conservation assessment, ecology and taxonomy, and a table distinguishing S. occidentale from S. bannisterioides, S. harleyi and S. paralias.